O controle do Estado acionista minoritário pelo Tribunal de Contas da União - Borges, Jéssica Suruagy Amaral (2018)
This study aims to analyse the limits of the control over the public investment in the social capital of private companies – due to their private profile – and it includes the critical analysis of the jurisprudence of the Federal Court of Audit (Tribunal de Contas da União) related to the subject. Contemporarily, the governmental business performance has been diversifying its possibilities. In the economic context, considering the administrative discretionary field, the public organs and entities have the choice to join the private initiative in a corporate partnership, sharing risks and responsibilities through the public investment in the share capital of private companies without acquiring the power of control. Despite of the legal regulation, the phenomenon of private companies with public minority shareholding denotes dissension regarding its characterization and the legal regime to be applied. The uncertainty seats on the external control over the phenomenon